Modernizacje techniczne w majątkach ziemiańskich w guberniach białoruskich w końcu XIX i na początku XX wieku - Jurkowski, Roman (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The conception of industrialization in reference to agriculture of six North-Western Gubernyias being a considerable part of the Taken Lands, has quite different dimension than in other sectors of partitioned Poland. Using two terms – industrialization of agricultural production and employment of modern methods of increasing this production – is more adequate here. The 1890s and the beginning of the 20th century are the years of intensive development in using new tools and agricultural machines in Polish manors, where wooden harrows and primitive ploughs had been still used in the 1870s, but at the turn of the 19th century, multiple furrow ploughs, cultivators, reaping machines, mowers and steam-threshers occurred. Many landlords invested money in alcohol distillery, increasing potatoes raising. Growing specialization of agricultural production can be clearly seen – Belorussian Gubernyias were the second in the production of milk and its products in European part of Russia. The reasons of this big modernizing development, as for the borderlands gubernyias, lie mainly in the falling profitability of traditional corn-growing and in the eagerness of Polish landlords for increasing profits from their properties.